Hpgd affects the progression of hypoxic pulmonary hypertension by regulating vascular remodeling - Meng He; Kelong Tao; Min Xiang; Jian Sun (BMC Pulmonary Medicine, 2023)
Abstract Background Hypoxic pulmonary hypertension (HPH) is a syndrome of abnormally elevated pulmonary artery pressure, and it is mostly caused by vasoconstriction and remodeling of the pulmonary artery induced by long-term chronic hypoxia. There is a high incidence of HPH, a short survival time of the patients, but currently no effective treatments. Methods In this study, HPH-related single cell sequencing (scRNA-seq) and bulk RNA sequencing (RNA-seq) data were downloaded from the public database of Gene Expression Omnibus (GEO) for bioinformatics analysis in order to find out genes with important regulatory roles in the development of HPH. 523 key genes were identified through cell subpopulation identification and trajectory analysis of the downloaded scRNA-seq data, and 41 key genes were identified through weighted correlation network analysis (WGCNA) of the bulk RNA-seq data. Three key genes: Hpgd, Npr3 and Fbln2 were identified by taking intersection of the key genes obtained above, and Hpgd was finally selected for subsequent verification. The human pulmonary artery endothelial cells (hPAECs) were treated with hypoxia for different periods of time, and it was found that the expression of Hpgd decreased in hypoxia-treated hPAECs in a time-dependent manner. In order to further confirm whether Hpgd affects the occurrence and development of HPH, Hpgd was overexpressed in hPAECs. Results Hpgd was confirmed to regulate the proliferation activity, apoptosis level, adhesiveness and angiogenesis ability of hypoxia-treated hPAECs through multiple experiments. Conclusions Downregulation of Hpgd can improve the proliferation activity, reduce apoptosis, and enhance adhesion and angiogenesis in endothelial cells (ECs), thus promoting the occurrence and development of HPH.